"Should I stay or should I go?": Weather forecasts and the economics of "short breaks" - Lorenzo Zirulia (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
The aim of this paper is to model the decisions of tourists and a monopolist firm when weather forecasts are available. Before deciding whether to go on holiday or not, but after the firm has decided and posted its price, tourists can look at weather forecasts. Our results show that the price chosen by the firm and the corresponding equilibrium profit are decreasing as a function of the accuracy of weather forecasts. Consumers, instead, are better off the more accurate weather forecasts become. Managerial and policy implications are also derived.
Keywords: D83; L12; L83; 330